1989
DOI: 10.1007/bf02621263
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inogranic lead inhibit neurite growth in vertebrate and invertebrate neurons in culture

Abstract: Neurons from brains of chick embryos and pond snails (Lymnaea stagnalis) were cultured for 3 to 4 d in the presence of no toxins, inorganic lead (PbCl2), or organic lead (triethyl lead chloride). In chick neurons, inorganic lead reduced the percentage of cells that grew neurites (IC50 = 270 microM total lead, approximately 70 nM free Pb2+) but did not reduce the number of neurites per cell or the mean neurite length. Triethyl lead reduced the percentage of cells that grew neurites (IC50 = 0.24 microM) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This total lead concentration is undoubtably much higher than the free lead concentration due to the chelating characteristics of cell culture medium. Measurements offree lead concentrations in cell culture medium with a lead-sensitive electrode by Audesirk et al (31) suggest that free lead levels in our experiments were in the nanomolar range. Thus, the current findings are consistent with our previous studies on leadinduced PKC translocation and enzyme activity in isolated 1 5 20 brain microvessels (11,12 also inhibited capillary-like tube formation (unpublished observation).…”
Section: Discussionsupporting
confidence: 46%
“…This total lead concentration is undoubtably much higher than the free lead concentration due to the chelating characteristics of cell culture medium. Measurements offree lead concentrations in cell culture medium with a lead-sensitive electrode by Audesirk et al (31) suggest that free lead levels in our experiments were in the nanomolar range. Thus, the current findings are consistent with our previous studies on leadinduced PKC translocation and enzyme activity in isolated 1 5 20 brain microvessels (11,12 also inhibited capillary-like tube formation (unpublished observation).…”
Section: Discussionsupporting
confidence: 46%
“…If the only active forms of the metal are the free ionic Pb in culture and the plasma Pb in blood, then the Pb concentrations may be approximately equivalent. Otherwise, they may be over 100-fold different (Audesirk et al, 1989;Tiffany-Castiglioni, 1993;Lidsky and Schneider, 2003). Furthermore, the relatively high concentrations required to elicit trophic effects may reflect regional-specificity of Pb effects.…”
Section: Discussionmentioning
confidence: 96%
“…No direct correlation exists between the Pb concentration in neuronal culture and that found in the blood of symptomatic children. In culture models, some studies have found the free ionic Pb concentration to be 100-1,000-fold lower than the original concentration (Audesirk et al, 1989). In human samples, Pb concentration in plasma is over 100-fold lower (0.27-0.70%) than that of whole blood (Hernandez-Avila et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…One micromolar Pb is approximately 20 µg/dl, a blood lead level can be examined easily, and brain Pb levels are 1-3-times those of blood lead in rats (Bradbury and Deane 1993). In experiments, the concentration of free Pb 2+ is approximately 1/1000 of total Pb (Audesirk et al 1989). Cells were treated with 1.0 µM Pb acetate in FBS-containing medium for various times as described in the figure legends.…”
Section: Materials and Methods Cell Culture And Identificationmentioning
confidence: 99%